Trapped in Temptation: Revealing The Factors That Lead to Fraud - Johan Arifin; Kurniawan, Kurniawan (Universitas Muhammadiyah Surakarta, 2025)
This research aims to empirically test various potential factors that influence the tendency to commit fraud. Fraud is a danger that always threatens the business and non-business worlds. Therefore, researchers are motivated to examine several factors that are suspected of influencing someone to commit fraud, namely the whistleblowing system, compensation suitability, and competence in addition to empirically testing ethical values as moderation. To obtain the necessary data, this study uses primary data using a questionnaire. The population in this study were employees in Finance and Banking companies in Indonesia. The number of samples in this study was 202 respondents. The data collection method was Snowball Sampling. The data analysis used was PLS-SEM. Based on the test results, it was found that a whistleblowing system with compensation suitability had a negative effect on the tendency for fraudulent acts, while competence had no effect on the tendency for fraudulent acts. This research also reveals that ethical values strengthen the relationship between the suitability of compensation and competence and the tendency for fraudulent acts, while ethical values weaken the relationship between the whistleblowing system and the tendency for fraudulent acts.